PENGEMBANGAN SILABUS PELATIHAN DALAM RANGKA PENINGKATAN KOMPETENSI PETUGAS PROTEKSI RADIASI BIDANG MEDIS - Hermawan, Nanang Triagung Edi (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
Ionizing radiation as part of nuclear energy has been implemented in medical fields for diagnostic and therapy intention. An important factor for achieving radiation safety in the utilizations of ionizing radiation sources is the presence of competent personal. A literature study on standard competencies of Radiation Protection Officer (RPO) for improving of regulation has been conducted. The improvement of regulation on RPO competencies should cover requirements for responsibility and authority, leveling and classification, education and training qualification, also personal competencies standards. Based on radiation risk in the utilization of ionizing radiation in medical fields, Medical RPO is leveling in to Medical RPO Level 1, 2, and 3. Medical RPO competencies standards should consider knowledge, skills, and attitudes aspects that comply with National Working Competency Standards that suitable for each RPO level. The identified competencies standard than should be expressed in to training subjects that divided as general, basic, main, and practical subjects. For each training subjects should be created detail basic competencies and working success indicators. This parameter becomes a basic for curricula, syllabus, teaching material and planning. The competency standard is basic for conducting training by personal training agency, and for arranging and conducting personal testing by personal certification agency. Keywords: ionizing radiation, personal, competencies, training, and Medical RPO.